Effect of cheesemaking with microparticulated whey proteins on the concentration of low molecular thiols in cheese - Niero, Giovanni; Sturaro, A.; Trentin, Anna Rita; Masi, Antonio; Marchi, Massimo De; Cassandro, Martino (Acta Agraria Kaposváriensis, 2014)
Aim of this work was to investigate different concentrations of microparticulated whey proteins (MWP) added during cheesemaking process on the recovery of low molecular weight thiols (LMT) in cheese. Historically, milk whey has been considered an industrial waste, because of its high cost of disposal and its polluting potential. In recent years the re - utilization of this waste represents an interesting perspective. Nowadays, several procedures are available to whey constituents recovery: some of the main are whey proteins (WP) and LMT. Whey ultrafiltration is the most common treatment to WP recovery. Thereafter, the WP undergo processes that lead to the production of protein aggregates (microparticulated-MWP), useful in different sectors of the food industry for their high gelling power and potential in LMT linkage. Mini-cheesemaking trial using milk standardized at 3.5% of protein with 3.0% or 4.0% MWP were carried out. Cheesemaking were performed in 6 days, 3 days for each treatment. Within a day, 3 replicates of the same treatment were carried out (n=18). The LMT of milk and whey were determined using RP - HPLC, while LMT in cheese were calculated by difference. Data were analyzed through a generalized linear model as fixed effects of the MWP concentration, replicate, and day of cheesemaking nested within MWP. Results showed that the quantified concentration of LMT in cheese were quite stable in both the percentages of MWP. The soluble properties of LMT represent a problem in their recovery in cheese; indeed beyond a certain concentration they are not retained in the curd, but are released in the whey.
Keywords: microparticulated whey proteins; RP - HPLC; thiols; whey protein